The economic impact of porcine reproductive and respiratory syndrome outbreak in four Chinese farms: Based on cost and revenue analysis - Zhang, Zhendong; Li, Zhi; Li, Hao; Yang, Shuqing; Ren, Fubo; Bian, Ting; Sun, Liumei; Zhou, Bin; Zhou, Lei; Qu, Xiangyang (Frontiers in Veterinary Science, 2022)
The economic impact after the outbreak of porcine reproductive and respiratory syndrome (PRRS) has been proven to be tremendous for pig production worldwide. However, the economic impact of the disease is not well understood in China. In previous study, we acquired and analyzed the main production data from management system before and after PRRS outbreak in four cases occurred in November 2014, March 2015, December 2016 and February 2017. The aim of this study was to analyze and quantify the economic losses of the four PRRS outbreaks in Chinese herds. A straightforward approach was used to calculate additional costs and decreased revenues based on the PRRS induced production deficiencies by average cost-of-production indices calculated from annual estimates of costs between 2014 and 2017. The results showed that economic losses varied between ¥668.14 and ¥1004.43 per sow in breeding herds from outbreak to regain the basic performance, with an average of ¥892.19 per sow, and the mean costs on the fattening herds (including nursery pigs) were ¥601.12 per sow, ranging from ¥318.64 to ¥937.14. Overall, the economic impact of PRRS on the whole herds was ¥1493.81 per sow. The majority of the losses were due to the reduction in the number of weaned piglets for breeding herds, and the increased feed cost (occupying 44.88%) was the primary source for fattening herds. Our study fills the gap in knowledge of PRRS economics in China, enriches the data for veterinary economics and re-stresses the necessity for producers and veterinaries to control PRRS effectively.